Experience of haemovigilance in Japan. (6th April 2018) - Satake, M.
Abstract : A haemovigilance system was established in Japan in 1993 by the Japanese Red Cross (JRC) headquarters, with the initial purpose of collecting reports of adverse transfusion reactions from medical facilities. Although this is a voluntary reporting system, the JRC, in co‐operation with medical facilities, collects almost all serious adverse reactions caused by blood transfusion. Non‐haemolytic transfusion reactions account for >90% of all reported events and transfusion‐transmitted infection (TTI) account for 5–6%. The JRC haemovigilance system is supported by laboratory analyses conducted in the JRC Central Blood Institute and other laboratories. The JRC collects pre‐ and post‐transfusion blood samples from patients who have experienced adverse reactions. These samples together with repository blood samples obtained from corresponding blood donations are analysed to investigate the pathogenesis of adverse events. Data obtained using these samples are helpful in increasing our understanding of transfusion‐related events such as TTI, transfusion‐related anaphylaxis and transfusion‐related acute lung injury (TRALI). Each country has its own history of establishing blood programmes. The relationship between government, blood facilities, transfusion societies and physicians or clinical fields may differ greatly between countries, and the structure of national haemovigilance systems will differ according to these relationships. Whatever haemovigilance system is established, extensive collaboration and adequate information exchange are essential among stakeholders. Strong leadership by a national transfusion society in addition to legislative measures is required if a comprehensive national haemovigilance system is to be established.